GI confidential - Limón, Martin, 1948- (Soho Crime, 2019)
South Korea, 1970s: A rash of armed robberies at local Korean banks doesn<U+2019>t concern the American military<U+2014>until a fatality occurs, and proof surfaces that US soldiers are behind the crimes. The case has been assigned to CID Agents Jake Burrows and Felix Slabem, but they certainly won<U+2019>t do anything that might make 8th United States Army look bad. So Sergeants George Sueño and Ernie Bascom have decided to step in and investigate the robberies<U+2014>and murder<U+2014>themselves. George and Ernie have their own problems to worry about, namely Katie Byrd Worthington, a pesky reporter for the Overseas Observer<U+2014>an unsanctioned English-language tabloid that has found strong roots in South Korea. Katie has published a story that implicates Army higher-ups in both sex trafficking and treason, and the pressure is on for the CID to disprove her claims. But what if they aren<U+2019>t false? As George and Ernie dig deeper into the case, they find themselves the targets of a very unflattering publicity campaign, but perhaps also something much more dangerous.